Imperialism, Buddhism and Islam in Siam: exploring the Buddhist secular in the Nangsue Sadaeng Kitchanukit, 1867 - Streicher, Ruth (Journal of Southeast Asian studies, 2021)
This article argues for understanding the reform of the Buddhist tradition in nineteenth-century Siam as a shift towards a secular conceptual grammar, and positions this shift within the dual imperial context of Siam. The binary conceptual structure that can be traced in the Nangsue Sadaeng Kitchanukit (Elaboration on major and minor matters, 1867) also included an opposition between Buddhism and Islam, documenting not only the epistemic marks of the Christian missionary encounter, but also the inner-political imperial context of Siam's hegemony over the Islamic sultanate of Patani.